Health Challenge as A Factor Affecting Health Insurance Purchase in Private Sector Organizations in Kwara State, Nigeria - Afolabi, Taofeek Sola (Academy of IRMBR, 2016)
This study attempts to investigate health challenge as a factor influencing health insurance purchase in private sector organizations, with special reference to Nigerian Bottling Company Plc as the case study. The study makes use of primary data that was sourced through a well-structured questionnaire. A total of one hundred (100) questionnaires were administered to the selected sample, while ninety five (95) were properly filed and returned. The person product moment correlation coefficient and the t-test were adopted for the data analysis. The result of the analysis shows that there exist a positive relationship between health challenges and health insurance purchase (r = 0.649** N= 95, P < 0.1). In the same line of analysis, the result of the t-test analysis reveal that both health challenges (t = 138.059, p = .000, μ = 4.5912) and health care challenge (t = 141.966, p = .000, μ = 4.5701) are significant at 1% level of significance. It was concluded that there is a significant relationship between health challenges and health insurance purchase and that there is a significant difference between health challenges and health care challenge as a predictor of health insurance purchase. It is recommended among others that health service providers must endeavor to render cutting edge service to their registered members through improving on the quality of drugs and attention to patients.
Keywords: Insurance; Health Insurance; Health Challenge; Purchase; Private Sector Organizations